Farmers Attitude towards Organic Farming in Uttar Pradesh (Indian Journal of Extension Education, 2024)
Organic farming helps in raising income and employment for farmers and hence agrarian economy, through improvement in agricultural productivity and sustainability in agricultural production. Therefore, keeping this in view a study was performed using stratified random sampling method in specifically Prayagraj district of rural Uttar Pradesh to analyse farmers’ attitude towards organic farming during 2023. The area under research was confined to two blocks of the selected district, Phulpur and Dhanupur with a sample of 80 farmers out of population. The independent and dependent variables selected for study of Farmers attitude were measured on different scales and data collected was analysed using basic statistical tools like percentages, frequency and chi-square test was applied to test goodness of fit and finally results were interpreted. Findings reveal that majority of the respondents (80%) had positive attitude towards organic farming and they are facing the problem of inadequate marketing facility for their produce. Further researches may be carried out in other areas so that generalization of results could be possible. Also, it is possible to consider the women folk in understanding the level of knowledge with respect to modern agriculture, organic farming, and organic foods.